The Influence Of Online Customer Reviews And Live Streaming On The Purchase Decision Of Skintific Products On Shopee - Risfian, Yusuf; Supriyono, Supriyono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to determine the influence of live streaming and online customer reviews on purchasing decisions of Skintific products on Shopee. Live streaming is an interactive feature that allows sellers to showcase and promote products in real time, enabling potential buyers to ask questions and receive immediate responses. This feature creates a sense of engagement and trust, which can significantly impact consumer interest and buying behavior. On the other hand, online customer reviews serve as a form of electronic word-of-mouth, where the experiences and opinions of previous consumers can shape the perceptions and decisions of prospective buyers. These reviews provide insights into product quality, effectiveness, and overall satisfaction, which are essential factors in the decision-making process. This research adopts a quantitative approach using a survey method, with data collected from 90 respondents who have both watched live streaming and read reviews related to Skintific products on Shopee. The questionnaire was developed using a Likert scale to measure perceptions across key indicators. The sampling technique used is non-probability sampling with a purposive sampling approach, targeting individuals who meet specific criteria relevant to the study. Data analysis was conducted using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method with the help of SmartPLS 4 software. The results indicate that both live streaming and online customer reviews have a positive and significant effect on purchasing decisions. These findings suggest that businesses should strategically optimize their live streaming content and actively encourage positive customer reviews in order to enhance consumer trust and drive product sales.